Assessing the quality of lettuce (Lactuca sativa L.) for nitrate and dry matter contents (Semiárida, 2020)
Lettuce (Lactuca sativa L.) is a vegetable of global consumption and his production has been increasing. The nitrate content in leaves is an important aspect of his quality, closely related to consumer health. In order to assess the quality of lettuce produced under cover, in terms of dry matter and nitrate contents in order to establish whether there were differences between times and dates harvest. To compare them, if they were within the limits established by the legislation of the European Commission. The work was conducted between December 2005 and December 2006, in an establishment located in Toay, Province of La Pampa. The results were analyzed using ANOVA by arrangement factorial of the information. For comparison of treatment means Tukey test (p ≤ 0.05) was used. The experimental unit was 400 m2, which extracted 8 lettuce plants representative of the crop, at 9 and 17 h, in a bimonthly. Fresh weight, dry weight and nitrate content of each plant were determined. The results of the analysis of dry matter showed highly significant differences between times and dates, while for nitrate only significant differences between dates. All samples are below the limits established by the legislation of the European Commission.
Keywords: lettuce; nitrate; dry matter; European Commission Legislation